2015
DOI: 10.1007/s00467-015-3210-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender and obesity modify the impact of salt intake on blood pressure in children

Abstract: Our results demonstrate an extremely high salt intake among 8- to 9-year-old Portuguese children. Higher salt intake was associated with higher systolic BP in boys, specifically in those who were overweight/obese. Longitudinal studies are needed to further evaluate the causal relationship between obesity and high BP and the mechanism by which salt intake modulates this relationship. Nonetheless, based on our results, we urge that dietary salt reduction interventions, along with measures to fight the global epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
5
17
0
1
Order By: Relevance
“…The opportunity to monitor both iodine and sodium excretion in a large sample lead us to estimate salt consumption in our study population. In spite of the limitation of applying the sodium excretion estimation equation validated for young adults, our results are comparable to those of a 24-h sodium excretion estimated among Portuguese children (6.4 ± 2.0 g/day in our study vs. 6.5 ± 2.2 g/day in Correia-Costa et al) [14]. The estimation of sodium intake in high risk iodine deficiency population groups from spot urine samples could be an opportunity for adequate monitoring of population means and progress towards public health goals [26].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The opportunity to monitor both iodine and sodium excretion in a large sample lead us to estimate salt consumption in our study population. In spite of the limitation of applying the sodium excretion estimation equation validated for young adults, our results are comparable to those of a 24-h sodium excretion estimated among Portuguese children (6.4 ± 2.0 g/day in our study vs. 6.5 ± 2.2 g/day in Correia-Costa et al) [14]. The estimation of sodium intake in high risk iodine deficiency population groups from spot urine samples could be an opportunity for adequate monitoring of population means and progress towards public health goals [26].…”
Section: Discussionsupporting
confidence: 84%
“…This approach was evaluated by comparing our results with recent data from a 24-h urine excretion in a similar Portuguese population [14].

For men: predicted 24-h urinary sodium excretion (mg/day) = 23 × {25.46 + [0.46 × spot sodium (mmol/L)] − [2.75 × spot creatinine (mmol/L)] − [0.13 × spot potassium (mmol/L)] + [4.10 × BMI (kg/m2)] + [0.26 × age (y)]}

For women: predicted 24-h urinary sodium excretion (mg/day) = 23 × {5.07 + [0.34 × spot sodium (mmol/L)] − [2.16 × spot creatinine (mmol/L)] − [0.09 × spot potassium (mmol/L)] + [2.39 × BMI (kg/m2)] + [2.35 × age (y)] – [0.03 × age2 (y)]}

…”
Section: Methodsmentioning
confidence: 99%
“…Of 1892 citations identified by the search, 13 studies from eight countries met inclusion criteria (Figure): 11 observational studies and two meta‐analyses . The primary outcomes of these 13 studies included mortality and cardiovascular events, blood pressure (BP) or diagnosis of hypertension, kidney disease, nonalcoholic fatty liver disease and obesity . Summary descriptions of the 13 included studies are listed in the Table and risk of bias assessments for all included studies are included in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…This culinary practice is common among the Mexican population. It has been observed that the addition of a condiment or other food to enhance the flavor of fruits and vegetables is a facilitator for their consumption among children (21); however, it is recommended to moderate their consumption to avoid health risks due to high sodium intake (22), and the possible adverse effects of chili in the digestive tract of children (23). After the intervention, a higher proportion of school children identified the health benefits of consuming V&F, indicating that the messages of the printed material together with the planning action of the consumption of V&F can ease the appropriation of information by children.…”
Section: Discussionmentioning
confidence: 99%